Effects of phosphorus and potassium fertilizers on dry matter accumulation, distribution and yield of relay strip intercropping soybean - LEI Ting; XIANG Da-bing; GUO Kai; YANG Wen-yu; LIU Zeng-yu; CHEN Xiao-rong (浙江大学学报. 农业与生命科学版)
The effects of phosphorus (P) and potassium (K) fertilizers on dry matter accumulation, distribution and yield of soybean were studied by randomized block design in relay strip intercropping system of maize-soybean. The results showed that dry matter accumulations of whole plant and each organ (root, stem, leaf and legume) at the full mature stage all increased with increasing K application amount, while increased at first and then decreased with the increase of P application amount, and the dry matter accumulations of whole plant and each organ all reached the highest under the P2K3 (P2O5 17 kg·hm-2, K2O 112.5 kg·hm-2) treatment. The changes of dry matter accumulations of stems and leaves in the whole period showed a single peak curve, and the changes of dry matter accumulation in whole period with the increase of K and P application amount were all similar to that of dry matter accumulation of whole plant (except seedling stage). The distribution proportion of the dry matter from plant to legumes increased with the increase of K application amount, while the distribution rate increased at first and then reduced with the increase of P application amount. But the changes of the distribution rate of the dry matter from plant to stems and leaves with the increase of P and K application were all opposite to that of legume. Increasing the P and K applications could improve the dry matter translocation amount and translocation ratio from vegetative organs to legumes, the contribution of dry matter accumulation amount to legumes and yield. The P2K3 treatment had the highest yield with 2 832.04 kg·hm-2, which was significantly higher than that of other treatments.